Pathogenicity of Spodoptera Litura Nuclear Polyhedrosis Virus to S. Litura F. Larvae and its Impact on Sycanus Leucomesus W. - James, Rubinsin Kotulai (1994)
Spodoptera litura Fabricius (Lepidoptera: Noctuidae) is a pest of many agriculture and forestry crops in several parts of the world including Malaysia. One of the natural enemies responsible for regulating field population of S. litura is a nuclear polyhedrosis virus (NPV). In this study, the S. filura NPV was tested for its actual pathogenicity to S. Litura larvae using eight viral doses ranging from 60 to 6 X 10⁸ PIBs/larva. The result of bioassay shows that LD50 LD90 and LD99 was 5.50 x 10⁴, 5.26 X 10⁸ and 9.26 x 10¹¹ PIBs/larva, respectively. The regression equation, Y = 3.47 + 0.32X , indicates that an increase of larval mortality was due to an increase in viral doses. The LT of the doses was eight, six and five days, respectively, with a regression equation of Y = 13.59 - 9.41X.